Psoriatic Dermal-Derived Mesenchymal Stem Cells Induced C3 Expression in Keratinocytes - Peng A; Lu F; Xing J; Dou Y; Yao Y; Li J; Li J; Hou R; Zhang K; Yin G (Dove Medical Press, 2022)
Aihong Peng,1 Funa Lu,1 Jianxiao Xing,1 Yu Dou,1 Yuanjun Yao,1 Juan Li,1 Junqin Li,1 Ruixia Hou,1 Kaiming Zhang,2 Guohua Yin1 1Shanxi Key Laboratory of Stem Cells for Immunological Dermatosis, Institute of Dermatology, Taiyuan Central Hospital of Shanxi Medical University, Taiyuan, People's Republic of China; 2Shanxi Key Laboratory of Stem Cells for Immunological Dermatosis, Institute of Dermatology, Taiyuan Central Hospital, Taiyuan, People's Republic of ChinaCorrespondence: Guohua Yin, Shanxi Key Laboratory of Stem Cells for Immunological Dermatosis, Institute of Dermatology, Taiyuan Central Hospital of Shanxi Medical University, No. 5, Dong San Dao Xiang, Jiefang Road, Taiyuan, People's Republic of China, Tel +86-0351-5656080, Email yinguohua1999@sina.comPurpose: Our recent studies found a splice region mutation in C3 accompanied by a significantly increased C3 in psoriatic peripheral blood. Mesenchymal stem cells (MSCs) are a key immunological suppression cell. We further investigate the regulation of MSCs on C3 in psoriasis.Patients and Methods: We analyzed the C3 and its upstream S100A9, S100A8 and downstream MCP1 in psoriatic and control skin, and in normal human epidermal keratinocytes (NHEKs) co-cultured with psoriatic versus control dermal-derived mesenchymal stem cells (DMSCs) by mRNA, iTRAQ (isobaric tags for relative and absolute quantitative) and simple Western analysis.Results: The mRNA and Simple Western analysis showed that the expression of C3, S100A8 and S100A9 are upregulated in psoriatic lesion (C3: mRNA, 9.23-fold, p = 0.0092; protein, 3.56-fold, p = 0.0244. S100A8: mRNA, 28.35-fold, p = 0.0015; protein, 4.68-fold, p = 0.0215. S100A9: mRNA, 79.45-fold, p = 0.0066; protein, 12.42-fold, p > 0.05). Moreover, the iTRAQ showed that C3 and S100A9 were significantly increased in NHEKs after co-cultured with psoriatic DMSCs compared to that of control DMSCs (C3: 3.40-fold, p = 0, FDR = 0; S100A9: 2.30-fold, p = 9.86E-241, FDR = 6.50E-239), verified by Simple Western. However, the expression of S100A8 and MCP1 was slightly different between the two groups.Conclusion: Our results suggest that psoriatic DMSCs contribute to the increased C3 expression in psoriatic lesion via upregulating S100A9, providing the theoretical basis for the role of C3 and DMSCs in the pathogenesis of psoriasis.Keywords: psoriasis, dermal mesenchymal stem cells, keratinocytes, C3, S100A9